Prototipe Robot Forklift Line Follower Dengan Metode Logika Fuzzy Berbasis Internet of Things - Pratama Yasfa, Arya; Ilyas Hadikusuma, Mohd; Mardianto, Eko; Hasan; Satriyo (Electrical Network Systems and Sources, 2025)
This research developed a prototype forklift line follower robot that applies the fuzzy logic method and is integrated with the Internet of Things (IoT) technology. fuzzy logic and integrated with Internet of Things (IoT) technology. This innovation This innovation is intended to improve efficiency and safety in material material management system in an industrial environment. The robot is designed to follow path using eight photodiode sensors and detects the color of objects through the TCS3200 sensor. A fuzzy logic method is used to handle uncertainty and dynamics in the trajectory, enabling more adaptive motion control. dynamics on the trajectory, allowing for more adaptive motion control. Sensor calibration showed a noticeable voltage difference between black (4.0 V) and white (0.16 V), with the use of a 10 kΩ resistor. Color sensor capable of recognizing six colors of objects based on a range of RGB values. The system is also capable of controlling the speed of the DC motor within the range of 0-255 PWM. Through IoT integration, information such as speed, object color, and delivery status can be monitored in real-time from a mobile device. can be monitored in real-time from a mobile device.   Keywords :, Forklift Robot, Line Follower, Fuzzy Logic, Internet of Things, Automation.